The Irish Education System and the Economy - McDonagh, Paddy (Maine Policy Review, 2000)
This article summarizes McDonagh’s remarks at the June 14, 1999 Maine Governor’s Economic Development Conference. He outlines Ireland’s educational strategies and investments of the past 30 years, as well as plans for the future, which include not only new educational initiatives but also significant investments in research and development. The educational roots of Ireland’s economic miracle include a concerted national effort to increase participation rates in higher education and a strategic effort to match the country’s education and training programs to the skills needs of global, high-tech companies. Such efforts have spanned decades, have required substantial investment, and have been sustained across changes in government administrations. Most importantly, such efforts have paid off. Ireland boasts one of the most highly skilled workforces in the world and is able to build economic success from its human capital by attracting the inward investment of growing high-tech, global companies.